IMPROVEMENT OF THE FORMATION OF MOTIVATION POLICY ON AGRICULTURAL ENTERPRISES - Чикуркова, А. Д.; Грей, Ю. М. (Podilian Bulletin: Agriculture, Engineering, Economics, 2020)
Motivational policy plays a large role in the effective management of personnel. The state of the economy and social relations in Ukraine and, equally important, the state of self-awareness of its citizens is unstable and complicated. During this period, it is especially important to act effectively in the field of enterprise personnel management. The situation is constantly changing and, accordingly, the approaches to the choice of effective methods of work with personnel must change. The methodological basis of the study is the dialectical method of cognition, determining the position of the theory of motivation of domestic and foreign scientific schools. In the course of the research, a systematic and logical approach to the scientific knowledge of the set of phenomena and processes related to the functioning of the personnel motivation system was applied, which revealed the main problems and prospects of improvement of the motivational policy in the enterprises. During the research, the methods of logical generalization and comparison were used to formulate the basic provisions and prerequisites for the formation of a motivational policy, an algorithm for managing a motivational policy; systematic analysis and synthesis, in particular, when substantiating the main directions of improvement of motivation policy at agricultural enterprises; statistical analysis - in the study of changes in the number and wages of employees in agriculture; logical generalization - when formulating conclusions. The article is devoted to the development of theoretical and methodological approaches to the formation of a modern effective motivational policy in agricultural enterprises. The main directions of improvement of motivational policy in agricultural enterprises are revealed. Systematic stages of implementation of motivational policy in agricultural enterprises. The trends of changes in the number and wages of employees in agriculture are determined. Based on the considered approaches, the algorithm of management of motivational policy in agricultural enterprises is formulated. The results of the study will expand the list of important directions of improvement of motivational policy, which are considered in the context of the algorithm of its management. The proposed algorithm for managing the improvement of motivational policy in agricultural enterprises will provide research and analysis of labor efficiency indicators, their monitoring, which will contribute to the increase of labor efficiency. Tracking factors of influence on the motivational orientation of management processes, deepening the study of motivational systems of change management in agricultural enterprises will be a promising area of research.